“Dinámica de absorción de los macroelementos en el cultivo de arroz (Oryza sativa L) bajo condiciones de riego.” - Valero Mora, Joel Omar (2019)
SUMMARY The cultivation of rice is a cereal, a short-cycle tropical crop and, at the same time, of great economic and nutritional importance, especially in underdeveloped or developing countries. At the present time the marketing of rice in Ecuador seeks to satisfy the domestic market first, therefore, its export will depend on the supply of the local market and the price of the domestic producer. The main factors that interfere in the production of rice are the climatic conditions, varieties not suitable for certain areas, incidence of pests, diseases and mainly the fertility of the soil where the macros and micro nutrients act because the plant responds according to the mobility of minerals. Studies carried out mention that the quantity of usable nutrients of the soil in the cultivation of rice varies with the cultivar, the production of biomass, the soil, the climate and the management. Therefore, very large differences in the extraction of nutrients by rice can be found in different conditions and latitudes. Specifically the main macroelements adsorbed from the soil from a crop are Nitrogen, Phosphorus, Potassium, Magnesium and Calcium, fulfilling specific functions. Soil fertility and macroelement dynamics in soil are associated with nutritional absorption. The absorption dynamics and the concentration levels of the macronutrients can vary according to the phenology and the organ that is analyzed, which may be leaves, stems or tissues. The deficiency of this element can generate chlorosis and delays in the development of rice. Unlike potassium, this element is essential in the nutrition of the plant and is transported by means of an APTase of the cell membrane, its deficiency can generate burning at the edges and weak stems. It is considered that 97% of the water fulfills the function of transporting dissolved elements or nutrients through the plant, it ascends through the root system to the foliar area. It is essential to make a specific diagnosis about the nutritional status of the plant. While the soil does not present deficiencies or toxicity of any macroelement, the rice crop will respond physiologically correctly. Keywords: Dynamics, Absorption, Fertilizers, Deficiency, Rice.